Social Services of Pakistan's Great Ulema Ahl-E-Sunnat and their Role in Promoting Islam (Research Study): Social Services of Pakistan's Great Ulema Ahl-E-Sunnat and their Role in Promoting Islam (Research Study) (International Research Journal on Islamic Studies (IRJIS), 2022)
Allah Almighty continued the lineage of Prophets and Messengers for the guidance of mankind. Then books and scriptures were revealed to these Prophets in their respective eras. The last link is the name of Sayyid-al-Anbiya Hazrat Muhammad (peace be upon him). After him, the scholars took up the cause of da’wah and its preaching and promotion. The role of scholars in society has always been a cause of religious, intellectual, and intellectual uprightness. There is a need for the readers to be made aware of the social services offered for the formation of the Islamic society, so that the people may know that the scholars have not only strived for the da’wah and preaching but they have also rendered social services for the welfare of society. Therefore, this article presents a research review of social services of some renowned Pakistan’s Sunni scholars i.e. Pir Karam Shah Al-Azhari, Maulana Shah Ahmad Noorani, and Dr. Tahir-ul-Qadri.
Keywords: Lineage; Guidance of Mankind; Scriptures; Da’wah; Preaching; Welfare; Religions; Social Services